The Role of IL-36 in the Pathophysiological Processes of Autoimmune Diseases - Chen, Wen-jian; Yu, Xiao; Yuan, Xin-Rong; Chen, Bang-jie; Cai, Na; Zeng, Shuo; Sun, Yuan-song; Li, Hai-wen (Frontiers in Pharmacology, 2021)
A member of the interleukin (IL) -1 superfamily was IL-36, which contained IL-36α, IL-36β, and IL-36γ, IL-36Ra. The heterotrimer complexes which was consisted of the bounding with IL-36 agonists (IL-36α, β, γ) and heterodimeric receptor complexes gave the signal through intracellular functional domains. And the functional domain could combine the downstream proteins and induce inflammatory responses. IL-36 agonists upregulated mature-associated CD80, CD86, and MHCII and inductively produced several pro-inflammatory factors by the IL-36R-dependent manner in dendritic cells (DCs), which had a strong ability to initiate the helper T (Th) cells differentiation. Up to date, the role of IL-36 in immunity, inflammation and other illnesses is magnificently of great importance. In this summary, we will briefly conclude the biological characteristics and the nearest advances of IL-36 in the development tendency and pathogeny of autoimmune diseases. This information may provide new directions and suggestions for the future research and the treatment of autoimmune diseases.